Distance education : definitions and glossary of terms - Schlosser, Lee Ayers; Simonson, Michael R. (Emerald Publishing Limited : IAP -Information Age Publishing, 2010)
Distance education is defined as institution-based formal education where the learning group is separated, and where interactive telecommunications systems are used to connect learners, resources, and instructors. This definition is expanded on in the 2009 yearbook of the Encyclopaedia Britannica, which validates this definition of the field. Distance Education: Definition and Glossary of Terms, 3rd Edition is unique in that it packages the terms together under one cover making this rapidly advancing complex topic easier to comprehend. The book addresses the complexities of terminology used in the field of distance education. In a time where distance education is becoming widely utilized across the globe, this at-a-glace approach makes it easier than ever to respond to the growing demand and questions about this subject matter.
Keywords: Distance education -- Dictionaries.; Distance education -- Philosophy.; elektronické knihy; Dictionaries.; Education -- Home Schooling.; Open learning, distance education.; Home schooling.; electronic books